A clinico‐demographic study of 344 patients with lichen planus pigmentosus seen in a tertiary care center in India over an 8‐year period. (23rd June 2019) - Vinay, Keshavamurthy; Kumar, Sheetanshu; Bishnoi, Anuradha; Aggarwal, Divya; Radotra, Bishan Dass; Parsad, Davinder; Sendhil Kumaran, Muthu
Abstract: Background: Lichen planus pigmentosus (LPP) is an acquired disorder of hyperpigmentation affecting certain racial and ethnic groups. Objective: To retrospectively analyze the demographic and clinical characteristics of LPP. Methods: Clinical and demographic records of all LPP patients attending our pigmentary clinic from January 2011 to June 2018 were reviewed. Results: Data of 344 LPP patients (229 females) were analyzed. Affected females had significantly higher age at onset ( P < 0.002) but lesser disease duration at presentation ( P < 0.001) as compared to males. Significant positive correlation between body surface area involvement and disease duration was observed ( r = 0.72). Personal history of atopy and accompanying autoimmune diseases were observed in 49 (14.24%) and 45 (13.08%) patients, respectively. Observed morphological patterns of LPP included diffuse ( n = 193, 56.1%); reticular ( n = 45, 13.1%); blotchy ( n = 41, 11.9%); and follicular ( n = 28, 8.1%). All the patients had a chronic and indolent course of disease with approximately half (49.2%) reporting satisfactory improvement with treatment. Conclusion: This is the largest clinico‐demographic study till date on LPP. A longer disease duration was associated with more widespread disease. Although the disease improved over time as per patient and physician global assessment, a complete clearance was rarely attained.